Smart-Pusdiklat: SMART-PUSDIKLAT: PROYEKSI MODEL SCENARIO BUILDING AND PLANNING DALAM TRANSFORMASI PUSDIKLAT BSSN - Firman Suprijandoko (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2020)
Smart-Pusdiklat is a major theme that can also be called a complete picture of a series of research puzzles within the scope of the education and training center. This research is a form of a puzzle for the transformation of the BSSN Pusdiklat organization. The research question that was raised was that as a result of organizational transformation, what kind of scenario projection model could be provided towards the Smart-Pusdiklat. Researcher discuss scenario building models and their planning which is developed through several scenarios. Where only limited by 2 key drivers, namely technology gap and security awareness. So as to create a variety of alternative scenarios that might color the perspective of the BSSN Pusdiklat organization. This study uses an exploratory research method with a qualitative approach. As a learning process, the planning delivery technique is conveyed using positive self-talk techniques to all members of the Pusdiklat. So that the presence of Smart-Pusdiklat will be felt in its role in the context of increasing the capacity of Human Resources for Cyber ​​Security and Passwords at the BSSN Training Center.